Welder’s Anthrax: A Review of an Occupational Disease - Marie A. de Perio; Katherine A. Hendricks; Chad H. Dowell; William A. Bower; Nancy C. Burton; Patrick Dawson; Caroline A. Schrodt; Johanna S. Salzer; Chung K. Marston; Karl Feldmann; Alex R. Hoffmaster; James M. Antonini (Pathogens, 2022)
Since 1997, nine cases of severe pneumonia, caused by species within the B. cereus group and with a presentation similar to that of inhalation anthrax, were reported in seemingly immunocompetent metalworkers, with most being welders. In seven of the cases, isolates were found to harbor a plasmid similar to the B. anthracis pXO1 that encodes anthrax toxins. In this paper, we review the literature on the B. cereus group spp. pneumonia among welders and other metalworkers, which we term welder’s anthrax. We describe the epidemiology, including more information on two cases of welder’s anthrax in 2020. We also describe the health risks associated with welding, potential mechanisms of infection and pathological damage, prevention measures according to the hierarchy of controls, and clinical and public health considerations. Considering occupational risk factors and controlling exposure to welding fumes and gases among workers, according to the hierarchy of controls, should help prevent disease transmission in the workplace.